The Place of Al-bardiji the Azerbaijani Hadithscholar and His Work Tabaqat Al-asma Al-mufradain Hadith Sciences - Shirinov, Rufat (Scholarya Demo Journal of Ruby, 2019)
He was born in Bardij, one of the centers of science and trade in Azerbaijan. He was forced to relocate to Baghdad due to certain circumstances of the period he lived. He continued his scholarly activity in Baghdad and was the student of famous local scholars. The Islamic Scholars spoke highly of him with the names hafiz, imam, sabt, sika, al-jalil and pillar of the hadith studies. During the period of Bardiji, Islamic stuides were developed and many works that add value to Islamic literature were created. He was involved in ilm al-Rijaal of hadith literature. This is the period when kutub al-sittah works were created. The period is also regarded as the Golden Age. It is also worth mentioning that the most valuable works in the field of jarh and ta’dil (science of criticism and praise) were written during this period. Al-Bardiji’s works related to the rijaal area of the hadithscience are well-known. Tabaqat al-Asma al-Mufrada by Bardiji is a valuable study dealing with single narrators of the hadith science, namely about thenarrators whose names were not mentioned more than once ever in the hadith literature. Some of them were criticized by scholars living in later years, nevertheless aforementioned work is very valuable in terms of being initial work of that style and in the terms of paving the way for subsequent studies.